2013
DOI: 10.1007/s00467-013-2572-y
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in paediatric kidney transplantation

Abstract: Caucasian paediatric patients are more likely to receive optimum treatment--a transplant from a living donor and fewer HLA mismatches. Further work is required to identify and address barriers to live donor transplantation among minority racial groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 35 publications
3
29
0
Order By: Relevance
“…[3] Further, there exist pervasive racial and ethnic disparities in kidney transplantation in both the adult and pediatric setting. [47] While much of the research examining this issue has been conducted in the United States, similar disparities have been identified in Australia[8], Belgium[7], Canada[9] the Netherlands[7], South Africa[10], and the United Kingdom[11] among others, indicating the global nature of this issue. Although it is important to note that some of these disparities may be the result of factors that are beyond the control of the medical system (e.g., co-morbidities and hereditary diseases that are associated with certain ethnic groups), [12, 13] studies have repeatedly demonstrated that differences in medical factors alone are not sufficient to explain the disparities in transplantation in their entirety.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…[3] Further, there exist pervasive racial and ethnic disparities in kidney transplantation in both the adult and pediatric setting. [47] While much of the research examining this issue has been conducted in the United States, similar disparities have been identified in Australia[8], Belgium[7], Canada[9] the Netherlands[7], South Africa[10], and the United Kingdom[11] among others, indicating the global nature of this issue. Although it is important to note that some of these disparities may be the result of factors that are beyond the control of the medical system (e.g., co-morbidities and hereditary diseases that are associated with certain ethnic groups), [12, 13] studies have repeatedly demonstrated that differences in medical factors alone are not sufficient to explain the disparities in transplantation in their entirety.…”
Section: Introductionmentioning
confidence: 82%
“…In 2005, Seikaly et al[19] published an analysis of United States Renal Data System (USRDS) data which reported that non-white status and lack of insurance was associated with delayed initiation of dialysis in children, although the etiology of this difference could not be explored given the limitations of the USRDS data set. Similarly, a recent analysis by Grace et al[8] demonstrated that aboriginal and minority children in Australia were significantly more likely to experience a late referral to nephrological care.…”
Section: Disparities In Initiating Transplant Evaluationmentioning
confidence: 88%
See 2 more Smart Citations
“…Ethnic disparities have also been identified outside the US. Indigenous children are less likely to receive a preemptive or a living-donor transplant in Australia [35], non-Western European origin is associated with reduced access to transplant in Belgium and the Netherlands [36], and ethnic minorities have lower rates of preemptive transplantation in the UK [37]. The reasons for these inequalities, including any contribution from underlying inequities, are subject to ongoing research [38].…”
Section: Inequalities In Access To Transplantationmentioning
confidence: 99%